The Flipped Classroom in a Terminal College Mathematics Course for Liberal Arts Students. (February 2018) - Carter, Christina L.; Carter, Randolph L.; Foss, Alexander H.
The purpose of this study was to assess the effect of flipping the classroom on final exam scores in a terminal general education college mathematics course for a diverse student population. We employed a quasiexperimental design. Seven instructors collectively taught 13 sections of each pedagogy (flipped/traditional). Six hundred thirty-two students participated. Common final exams were graded concurrently. Mixed-model analyses were performed. Students in flipped sections scored 5.1 percentage points higher on average than those in traditional sections (p = .02) when controlling for math SAT and financial aid status, an improvement of 7.8 points among Black students (p < .01) and 1.0 points among Whites (p = .67). The estimated average difference between White and Black students, conditional on covariates, was 5.2 percentage points in traditional sections (p < .01) and –1.6 in flipped sections (p = .39). The 6.8-point difference in achievement gap between pedagogies was statistically significant (p < .01). Flipping the classroom was associated with improved student performance, particularly among Black students.